ANALISIS PENDEKATAN STEM DENGAN MODEL PBL TERHADAP KEMAMPUAN MATEMATIS SISWA DALAM PENDIDIKAN MATEMATIKA - Mia Aulia Vikayatri (UNEJ e-Proceeding, 2022)
The emergence of the era of disruption due to rapidly developing technology has had many impacts on life. One of them is changes in the world of education, including mathematics education, that require renewal. This article aims to analyze the STEM (Science, Technology, Engineering, and Mathematics) approach with the PBL (Problem Based Learning) model on students' mathematical abilities in mathematics education/learning. The research method used is a literature study using data analysis techniques consisting of three stages, namely organize, synthesize, and identify. The data analyzed in this study is the result of reflections from several articles in both national and international journals. The results describe the STEM approach with the PBL model on students' mathematical abilities. Based on the results and discussion, the STEM approach with PBL model can improve students' mathematical proficiency, such as problem-solving skills, creative thinking, critical thinking, mathematical connections, mathematical communication, mathematical literacy, mathematical understanding, and positive student responses. These abilities are needed in the era of disruption and industrial revolution 4.0. The advice given is that further research is needed on the implementation of the STEM approach with the PBL model in mathematics education/learning to improve students' mathematical abilities. Keywords: mathematics ability, mathematics education, problem-based learning, STEM approach